2023
DOI: 10.3390/cancers15082306
|View full text |Cite
|
Sign up to set email alerts
|

Erector Spinae Plane Block versus Paravertebral Block after Thoracic Surgery for Lung Cancer: A Propensity Score Study

Abstract: Introduction: The prevention of respiratory complications is a major issue after thoracic surgery for lung cancer, and requires adequate post-operative pain management. The erector spinae plane block (ESPB) may decrease post-operative pain. The objective of this study was to evaluate the impact of ESPB on pain after video or robot-assisted thoracic surgery (VATS or RATS). Methods: The main outcome of this retrospective study with a propensity score analysis (PSA) was to compare the post-operative pain at 24 h … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…To date, evidence supporting the use of ESPB in robotic surgery is very limited and of low-moderate quality. A recent retrospective study by Durey et al [ 62 ] showed that ESPB is associated with less post-operative static and dynamic pain at 24 h than PVB after robot-assisted thoracic surgery for lung cancer, with a high safety profile. Moreover, a randomized controlled trial [ 63 ] on sixty adult patients undergoing minimally invasive thoracic surgery compared a single-shot ESPB to serratus anterior plane block before surgery on the quality of patient recovery at 24 h. In this study, ESPB provided superior quality of recovery, lower morbidity, and better analgesia after robotic surgery.…”
Section: Erector Spinae Plane Blockmentioning
confidence: 99%
“…To date, evidence supporting the use of ESPB in robotic surgery is very limited and of low-moderate quality. A recent retrospective study by Durey et al [ 62 ] showed that ESPB is associated with less post-operative static and dynamic pain at 24 h than PVB after robot-assisted thoracic surgery for lung cancer, with a high safety profile. Moreover, a randomized controlled trial [ 63 ] on sixty adult patients undergoing minimally invasive thoracic surgery compared a single-shot ESPB to serratus anterior plane block before surgery on the quality of patient recovery at 24 h. In this study, ESPB provided superior quality of recovery, lower morbidity, and better analgesia after robotic surgery.…”
Section: Erector Spinae Plane Blockmentioning
confidence: 99%
“…Results are debated concerning operative lymph node staging, and nodal upstaging in open surgery, VATS, or RATS [ 50 , 51 , 52 , 53 , 54 , 55 , 56 ]. Thanks to advances in anesthesia [ 57 ] and surgery, the mortality rate of lung surgery has decreased over the years [ 58 , 59 ]. Today, the 30-day mortality rate has further decreased to 2% after open lobectomy, 1.3% after minimally invasive lobectomy, and less than 1% after segmentectomy [ 47 , 60 , 61 ].…”
Section: Advances In Thoracic Surgery—the Evolving Landscape Of First...mentioning
confidence: 99%
“…These techniques can lead to smaller incisions, reduced tissue trauma, and faster recovery [ 3 ]. Additionally, optimized pain management strategies, such as the use of regional anesthesia or nerve blocks, are employed to minimize postoperative pain and facilitate early mobilization [ 57 ]. The postoperative phase of the ERAS program focuses on early recovery and rehabilitation.…”
Section: Advances In Thoracic Surgery—the Evolving Landscape Of First...mentioning
confidence: 99%
“…ESPB is commonly used for postoperative analgesia, particularly in patients undergoing thoracotomy for lung cancer. Nonetheless, existing studies assessing its postoperative analgesic effect have primarily focused on short-term efficacy [7]. Additionally, two cases of continuous ESPB for pain palliation in Pancoast tumors and pleural mesothelioma have been reported [8,9].…”
Section: Introductionmentioning
confidence: 99%